2014
DOI: 10.5620/eht.e2014016
|View full text |Cite
|
Sign up to set email alerts
|

Nanometrology and its perspectives in environmental research

Abstract: ObjectivesRapid increase in engineered nanoparticles (ENPs) in many goods has raised significant concern about their environmental safety. Proper methodologies are therefore needed to conduct toxicity and exposure assessment of nanoparticles in the environment. This study reviews several analytical techniques for nanoparticles and summarizes their principles, advantages and disadvantages, reviews the state of the art, and offers the perspectives of nanometrology in relation to ENP studies.MethodsNanometrology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The second reason is that the techniques based on light scattering like DLS require a higher concentration of NPs solution which is more likely to lead to aggregation. Consequently, these aggregated NPs have a disproportionate influence on the analytical signal (Kim et al 2014 ; Domingos et al 2009 ). The colloidal stability results showed that there was not any aggregation or change in hydrodynamic diameter of G 4 @IONPs after 28 days; it revealed that these MNPs had great colloidal stability which is a prerequisite for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason is that the techniques based on light scattering like DLS require a higher concentration of NPs solution which is more likely to lead to aggregation. Consequently, these aggregated NPs have a disproportionate influence on the analytical signal (Kim et al 2014 ; Domingos et al 2009 ). The colloidal stability results showed that there was not any aggregation or change in hydrodynamic diameter of G 4 @IONPs after 28 days; it revealed that these MNPs had great colloidal stability which is a prerequisite for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Bigger particles contribute to increasing the light scattering and shifting the measured size toward larger values. 34,35 The polydispersity of G 4 @IONPs as measured Table 2 The effect of most crucial parameters in IONPs synthesis. The effect of an increase of these parameters (in an optimum range) was shown on bare IONPs characteristics Increase 40 -- Abbreviation: IONPs, iron oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the standardization of nanohybrids is necessary not only to improve our scientific understanding of the underlying fundamental processes responsible for the generated analytical signals, but is also closely linked to the quality control concepts of the systems to promote their industrial applications. Thus, the general role of nanometrology can be summarized by the following formula [79][80][81][82][83][84][85]:…”
Section: A B Cmentioning
confidence: 99%